Determinants of infant and child mortality in the Philippines (1983-2003) - Alcantara, Astrid A.
This study used the Cox proportional hazards model with the 2003 National Demographic Survey to identify which socioeconomic, demographic, and proximate determinants dominate in affecting infant and child mortality in the Philippines within the five-year period between 1998-2003. Comparing partial socioeconomic determinants model with a more complex model (addition of proximate determinants model) and partial proximate determinants model with a more complex model (addition of socioeconomic determinants model) reveals that the proximate factors are more prominent than the socioeconomic factors in exerting net influence on infant and child mortality. However, the impact of proximate factors is more dominant with infant mortality than with child mortality. The effects of the socioeconomic factors operate through the significant proximate factors. Educational attainment of the mother of the births and socioeconomic status at the household level remain significant in all the models. However, they significantly interact in affecting infant and child mortality. That is, children born to the poor sector of our population face lesser risks of infant and child death if their mother has completed at least secondary education relative to those who have reached primary education or no education at all. Among children born of mothers who had no education at all or reached primary level of education, those who belong to the non-poor sector face lesser risks of child death compared to those belonging to the poor low educated sector. All the hypothesized proximate factors, breastfeeding, delivery assistance and place of delivery remain important net of the confounding effects of the other important variables. Breastfeeding reduces the risk of infant mortality while assistance in delivery and place of delivery interact with preceding birth interval and educational attainment in affecting infant mortality. That is, a child delivered with the assistance of a health practitioner or a non-health practitioner, faces lower risks of infant death by 54.0 and 46.8 per cent respectively, if his/her mother has college or higher education compared to his/her counterparts who were delivered with the assistance of a non-health practitioner and born to mothers with not education or who reached primary level, those who were delivered with the assistance of a health practitioner face lesser risks of infant death by more than half. Of the demographic/maternal factors (children ever born, maternal age, preceding birth interval) children ever born and preceding interval are net predictors. The greater the number of children ever born the mother of the index child has, the greater risk of infant and child mortality of the index child. While preceding birth interval significantly interacts with assistance in delivery, examination of its direct effects on infant and child mortality shows that children preceded by longer preceding birth intervals face significantly lower risks of infant and child death, relative to those preceded by shortest birth interval of 7-19 months.